Non-thermal atmospheric pressure plasma jet applied to inactivation of different microorganisms - Nishime, T. M.C. [UNESP]; Borges, A. C. [UNESP]; Koga-Ito, C. Y. [UNESP]; Machida, M.; Hein, L. R.O. [UNESP]; Kostov, K. G. [UNESP] (Elsevier, 2017)
Non-thermal atmospheric pressure plasma jets (APPJs) are capable of generating cold plasma plumes that are not confined by electrodes, which makes them very attractive for bio-medical applications. In the present work, the inactivation efficiency of cold APPJ was evaluated against three pathogenic microorganisms with different cell wall characteristics. The Gram-positive bacterium Enterococcus faecalis (ATCC 29212), the Gram-negative bacterium Pseudomonas aeruginosa (ATCC 15442) and the fungus Candida albicans (SC 5314) were plated on standard Petri dishes filled with specific culture media. The plasma jet with mean power of 1.8 W was directed perpendicularly on agar plates and the system was flushed with pure helium at two different flows, 2.0 and 4.0 SLM. During the treatments, time and distance between nozzle and agar were varied. The presence of excited reactive species was confirmed by optical emission spectroscopy. Scanning electron microscopy (SEM) was applied for investigation of cell morphology. The microbicidal efficiency was evaluated by measuring the area of inhibition zone (where there was no cell growth). For different flows of helium, no significant difference of inhibition zone size was noted for the same microbial species. However, high flows led to formation of non-homogenous inhibition zones, presenting microcolonies distributed through the inactivated region. The Gram-positive bacterium was more susceptible to the plasma antimicrobial effects than the other microorganisms.
Keywords: Cold atmospheric plasma; Decontamination; Plasma jet